Ritualizing the Everyday: The Dangerous Imperative of Hospitality in Apiao, Chiloé. Issue 2 (1st June 2019) - Bacchiddu, Giovanna
Abstract : Based on an analysis of ethnographic data collected in Apiao, Chiloé, this article offers a view of relations as inescapably fraught connections between different entities. These relations are articulated in highly ritualized hospitality practices involving reciprocal exchange of food and drinks in a domestic space. Cutting across established, contrasting analytical categories, such as consanguines/affines and friends/enemies, hospitality practices reveal the immanence of otherness. Relations can occur only among different/differentiated individuals and are always expressed through an alternation of the contingent positions of host and guest, where one offers and another receives. In hospitality interactions, sameness is denied and transformed into otherness, revealing the importance of asymmetry and disclosing the latent hostility and potential danger implicit in relations. The other is first and foremost a dangerous and unpredictable guest.